Innovation, sustainability and humanization of public space as prime factors for competitive tourism development - Mantilla Echeverría, Juan Manuel (Tierra Infinita, 2019)
The main objective of this paper is to analyze how competitive tourism development currently depends on several factors, including innovation, sustainability and humanization of public space. These factors make it possible to generate resilience and an attractive habitat first for residents and citizens. as a consequence, to national and international tourists and visitors, the main responsible for applying these factors are the local governments, with greater emphasis the municipalities that with appropriate public policies can capture these factors in the development of cities, especially in urban areas where The largest number of inhabitants is concentrated and they are the distribution axis of visitors and tourists to nearby destinations. In addition, currently a factor of attraction of cities for the realization of various types of tourism such as events, conferences and meetings is the quality of development of cities in various aspects of daily life as public spaces, media of transport, technology, culture and art. The more innovative, sustainable and human the city, the more successful it will be as a tourist destination.